2021
DOI: 10.1093/burnst/tkab012
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities of scars in China: a national study based on hospitalized cases

Abstract: Background Scar comorbidities seriously affect the physical and mental health of patients, but few studies have reported the exact epidemiological characteristics of scar comorbidities in China. This study aimed to investigate the prevalence of scar comorbidities in China. Methods The data of 177,586 scar cases between 2013 and 2018 were obtained from the Hospital Quality Monitoring System based on the 10th edition of the Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Though the molecular and cellular mechanisms of scar formation for example through major involvement of matrix metalloproteinases and their inhibitors are well known, their effect and functions are not completely understood when they are induced by laser therapy. It is perhaps this lack of understanding that has led to several trials focussing on laser type, duration and optimal timing being conducted in an endeavour to minimise heterogeneity in outcomes [ 33 , 34 ]. This meta-analysis aimed to address this heterogeneity by considering variables such as timing of treatment after injury, laser type, optimal spacing for laser intervention and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Though the molecular and cellular mechanisms of scar formation for example through major involvement of matrix metalloproteinases and their inhibitors are well known, their effect and functions are not completely understood when they are induced by laser therapy. It is perhaps this lack of understanding that has led to several trials focussing on laser type, duration and optimal timing being conducted in an endeavour to minimise heterogeneity in outcomes [ 33 , 34 ]. This meta-analysis aimed to address this heterogeneity by considering variables such as timing of treatment after injury, laser type, optimal spacing for laser intervention and complications.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that fat grafting can effectively reduce the degree of scar itching and pain of patients and improve their comfort. Itchy and painful scars are the most common clinical symptoms that not only affect the quality of life of patients but also damage their psychological health [21,22] . When caring for such patients, clinical nurses should actively assess the level of itching and pain and intervene as early as possible.…”
Section: Fat Grafting Can Reduce the Degree Of Scar Itching And Painmentioning
confidence: 99%